The making and performance of Alyona - Godman, R (2011)
Alyona is a 1-hour continuous set, presented as a live performance of Poetry, Hip-Hop and Immersive Sound.  The aim is to engage audiences through performance and documentation by offering unique and unrepeatable live events where the use of technology is transparent and visual. Audience perception of ‘liveness’ is a central component of the performance. We actively combine unlikely juxtapositions of place, material and style. This poster discusses the interdisciplinary relationships found within the work and methods of delivery for linear narrative including aesthetic considerations of ‘liveness’. This poster discusses the interdisciplinary relationships found within the work and methods of delivery for linear narrative including aesthetic considerations of ‘liveness’.